Molecular characterization of Klebsiella pneumoniae isolated from different clinical sources in Eastern and Western Regions of Saudi Arabia Tertiary Hospitals - Zahra ALBrahim; Nasreldin Elhadi; Faye Aldehalan; Asif A. Jiman-Fatani; Dalya M. Attallah (PeerJ, 2026)
Introduction The prevalence of extensively drug-resistant (XDR) and multidrug-resistant (MDR) strains worldwide has limited the ability of antimicrobial therapy to treat severe bacterial infections. The emergence and rapid global dissemination of carbapenemase-resistant Klebsiella pneumoniae (CRKP) strains occluded the therapeutic use of carbapenems, the last resort of β-lactams. In Saudi Arabia, major outbreaks of carbapenemase-producing Enterobacteriaceae have been reported, with approximately a 90% prevalence rate of CRKP strains. In this study, we aimed to delineate the prevalence and resistance patterns of the CRKP isolates in clinical samples from tertiary hospitals in the Eastern and Western regions of Saudi Arabia. Methods CRKP isolates were tested for carbapenem resistance using the disc diffusion method. Molecular screening and identification of these isolates for carbapenemase genes and conducted molecular genotyping using Enterobacterial Repetitive Intergenic Consensus Polymerase Chain Reaction (ERIC-PCR) DNA fingerprinting to map clonal relatedness. Results CRKP was identified in 112 clinical samples, all showing resistance to standard antimicrobials and at least one carbapenem. Molecular investigation of these CRKP isolates revealed a high epidemiological prevalence of Klebsiella pneumoniae carbapenemase (KPC) (91.1%) along with Oxacillinase-48 (OXA-48) (a type of class D β-lactamase) (92.9%), while New Delhi metallo-β-lactamase (NDM) was only observed in the Western region. ERIC-PCR fingerprinting was able to group strains into 12 distinct clusters with more than 95% genetic similarity. Conclusion This may indicate the attainment of an endemic state of the KPC genes, highlighting the need for an urgent establishment of stringent containment policies. These findings indicate the broad distribution of carbapenemase-producing Klebsiella pneumoniae in both regions, highlighting the urgent need for enhanced surveillance and strengthened infection control strategies. The molecular genotyping using ERIC-PCR showed a high level of genetic similarity among isolates, with limited genetic variability.